1980
DOI: 10.1115/1.3183853
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and Controlling the E.D.M. Process

Abstract: Extensive investigations were carried out to study the emitted radiation during the E.D.M. process. It was found that radiation from the region of the gap between the electrode (tool) and the workpiece is significantly different when the following four conditions: open voltage, effective discharge (sparking), arc and short circuit occur during the E.D.M. process. The sparking condition is accompanied by a comparatively high radiation level at radio frequencies above 1 MHz. During arcing, however, although rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…It has also been shown that the noise waveform of discharges between switch contacts is influenced by the choice of material [21] and electrode area [22]. In the late 1970s, early work showed that it was possible to use RF transmissions to distinguish between open-circuit, spark, arc, and short-circuit conditions in macroscale serial-mode EDM [23], [24]. At the microscale, particularly for batch mode, process monitoring is even more critical.…”
Section: B Sensing Debris-dominated Machiningmentioning
confidence: 98%
“…It has also been shown that the noise waveform of discharges between switch contacts is influenced by the choice of material [21] and electrode area [22]. In the late 1970s, early work showed that it was possible to use RF transmissions to distinguish between open-circuit, spark, arc, and short-circuit conditions in macroscale serial-mode EDM [23], [24]. At the microscale, particularly for batch mode, process monitoring is even more critical.…”
Section: B Sensing Debris-dominated Machiningmentioning
confidence: 98%
“…In order to over come from such circumstances a skilled operator is required to take a corrective action to stable the machine by adopting proper corrective measures. Further different online controllers were developed; polynomial function based Abductive network [89,94], pulse discriminating type analyser [95], radio frequency analyser [96,97], neutral network base [90,98], fuzzy base pulse discriminator system [99,100] and digital signal procesing base [101]. These controllers identifies EDM process pulses and discriminates it and take proper corrective measures to stabilise the machine.…”
Section: Pulse Discriminatingmentioning
confidence: 99%
“…intense Radio Frequency (RF) signal is emitted due to the high rate of current change [93][94][95]. The intensity of this signal was found to drop rapidly as arcing is about to take place.…”
Section: Radio Frequencymentioning
confidence: 99%